The Neoplastic Whorls-Soft Tissue Perineurioma - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2020)
Perineurioma is an exceptional, benign neoplasm entirely composed of neoplastic perineurial cells and arises from the peripheral nerve. Pertaining to location, the neoplasm predominantly demonstrates configurations such as intra-neural or extra-neural, confined to the soft tissue. Perineurioma was initially scripted by Lazarus and Trombetta in 1978 and is additionally nomenclated as localized hypertrophic neuropathy1. Extra-neural soft tissue perineurioma and mucosal (intestinal) perineurioma are frequent, in contrast to intra-neural perineurioma or localized hypertrophic neuropathy subtype12.
Keywords: Soft tissue perineurioma